Faktor-Faktor yang Mempengaruhi Partisipasi pada Sistem Agroforestri di Areal Kerja Hutan Kemasyarakatan Catur Rahayu - Stephani, Sintiya; Hamzah, Hamzah; Syarifuddin, Hutwan (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The Catur Rahayu community forest (HKm) is located in Catur Rahayu Village, Dendang Subdistrict, East Tanjung Jabung Regency, Jambi Province. In 2019, 81% of their land experienced fire. Some of them have carried out replanting, but some have not yet done so due to limited funds, especially for land preparation activities. From a socio-economic aspect, the majority of GAPOKTANHUT Catur Rahayu members work as farmers and have education only up to elementary school, so they do not have much money, knowledge and knowledge to maximize their land management. This research aims to analyze participation, socio-economic factors, and the relationship between these two variables. The analysis method uses the Spearman's rho correlation test. The results of the research show that the level of participation of GAPOKTANHUT Catur Rahayu members at all stages of HKm activities is in the high category with a percentage of 36.78%. Based on indicators of socio-economic factors that correlate with participation in HKm activities, namely non-formal education, land area, income, cosmopolitan, leadership, and incentives, while socio-economic factors that are not correlated with participation in HKm activities are age, formal education, distance to HKM land, and number of dependents. In total there is no significant relationship between socio-economic factors and the participation of GAPOKTANHUT Catur Rahayu members.